Cybersecurity: Is It Worse than We Think? - Maurer, Chris; Kim, Kevin; Kim, Dan; Kappelman, Leon A. (Communications of the ACM, 2021)
The article analyzes the state of cybersecurity in various organizations and businesses as of early 2021 based upon research conducted that attempted to glean whether firms hired information officers, purchased cyber insurance, and the degree of consideration given to cybersecurity during software development, change management, and strategy. The authors also recommend that organizations prioritize cybersecurity by hiring executive-level information officers (CISOs) to better implement security practices.